Nanogap-engineered Pd sensors for self-powered hydrogen detection via triboelectric mechanism - Kwon, Yeong Min; Lee, Seung Yong; Do, Soo Jee; Park, Sang Jeong; Kim, Hyung-Seok; Chun, Dong Won; Hoang, Nhat Nam; Lee, Jae Won; Lee, Kyu Hyoung; Han, Gi Hyeon (Elsevier BV, 2025)
Hydrogen gas sensors with self-powered capabilities are crucial for real-time monitoring and safety applications. In this study, we present a triboelectric-based hydrogen gas sensor that dynamically modulates its effective electrode area in response to hydrogen concentration, thereby altering its triboelectric output. Hydrogen adsorption triggers the selective closure of nanogaps within the Pd layer, effectively increasing the conductive electrode area and enhancing triboelectric charge generation. As hydrogen concentration rises from 0.1 % to 2 %, the nanogaps progressively close, resulting in a corresponding increase in triboelectric output voltage. At higher concentrations, near-complete closure of nanogaps maximizes electrode connectivity and charge transfer efficiency. This mechanism enables hydrogen concentration-dependent output without the need for an external power source. The integrated triboelectric nanogenerator (TENG) framework allows the sensor to function as both a real-time hydrogen detector and an energy-harvesting device. This scalable, dual-functional platform offers a promising approach for next-generation gas sensors with applications in hydrogen-powered systems, industrial safety, and environmental monitoring.